Population parameters of planktonic shrimp, Lucifer intermedius (Decapoda: Sergestidae) from Sungai Pulai seagrass area Johor, Peninsular Malaysia - Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Osman, Norhafizah; Che Cob, Zaidi; Saad, Che Roos (Penerbit Universiti Kebangsaan Malaysia, 2010)
Growth, mortality and recruitment of the sergestid shrimps Lucifer intermedius, collected from the Sungai Pulai seagrass area in Johor, Peninsular Malaysia was investigated between April 2007 and December 2007 using monthly length-frequency data. The shrimps were collected during the day by subsurface towing of a Bongo net with a mesh size of 500 μm for 30 minutes. Total length was measured monthly for 50 individuals and the estimated extreme length was 10.42 mm. The von Bertalanffy growth parameters, K and L∞ were estimated as 1.40 yr-1 and 11.10 mm, respectively. The growth performance index (φ’) was 2.237 while total mortality (Z) was calculated at 5.32 yr-1. The natural and fishing mortality was 2.99 yr-1 and 2.33 yr-1, respectively. The recruitment pattern of L. intermedius was continuous throughout the year with two major peaks. The exploitation rate (E) was estimated at 0.44. This indicates that fishery status of L. intermedius in the Sungai Pulai sea grass area of Johor Strait is below the optimum level of exploitation (E < 0.50).